Paragangliomas and syringomyelia in Tetralogy of Fallot-A case report and literature review - Guha, Anasuya; Antonova, Petra; Zelinka, Tomas; Vicha, Ales; Pacak, Karel; Chovanec, Martin (Clinical case reports, 2024)
Pulmonary atresia with ventricular septal defect and major aortopulmonary collateral arteries, paragangliomas, and syringomyelia are uncommon diseases. Furthermore, in the absence of any genetic link and with less than five reported adult patients surviving unrepaired rare form of Tetralogy of Fallot, our case shows noteworthiness. The possibility of definitive treatment of these conditions is rendered unsafe due to this persistent defect. Thus, management and ongoing survival of this patient remains complex and challenging.
Keywords: syringomyelia; PA/VSD/MAPCAs; 22q11DS; cyanotic congenital heart disease; succinate dehydrogenase complex subunit D mutation; carotid body tumor